Ablação por radiofreqüência do ventrículo esquerdo no rato: um novo modelo de insuficiência cardíaca com tamanhos de infarto do miocárdio semelhantes e baixa mortalidade - Antonio, Ednei Luiz [UNIFESP] (2010)
The Myocardial Infarction (MI) in rodents is the most frequently used animal model to reproduce experimentally the Congestive Heart Failure (CHF) in humans. Surgical closure of the anterior descending coronary artery (ADCA) is the method traditionally used to obtain the experimental MI decades. This model is well validated to simulate CHF, as evidenced by the large number of publications that provide relevant information significantly. The coronary artery ligation in rats is inherently associated with infarcts of variable size, and in some cases, absence of myocardial necrosis. Another unfavorable factor is the high rate of mortality after coronary occlusion (CO). The purpose of this study was to standardize a new model of CHF secondary to MI by applying radio frequency electric current in the left ventricle (LV), and analyze the characteristics of the model. To this end, we used 210 Wistar-EPM, male and female, in groups, operated by the traditional method of coronary occlusion, and radiofrequency ablation without surgical intervention or control group. After the promotion of MI, animals were separated into groups of one and four weeks for evaluation, which were anesthetized and sequentially assessed by echocardiography (ECHO), hemodynamic, myocardial mechanics, and pathological. The transmural infarction occurred in all cases operated ablation with immediate mortality of 7.5%. CO animals were included only MI> 40% LV. The variability in the size of the MI were lower in rats Ab (x ± SD: 45 ± 8%) when compared with coronary occlusion (CO, 40 ± 19% SD). The echocardiography and hemodynamic study showed comparable increases in the sizes of the LV end-diastolic pressure and pulmonary water content in one and four weeks post-MI. Myocardial mechanics six weeks post-MI were compatible in the inotropic and lusitropic dysfunction. Histopathological evaluations were identified lesions similar to those that occurred after CO, with complete healing phase in four weeks. Ab IM VE originated with similar size and low mortality. Resulted in histopathological changes, and ventricular dilation, mechanical dysfunction and myocardial failure. Results reproducing the IM by CO.